Are banks using hidden reserves to beat earnings benchmarks? Evidence from Germany - Sven Bornemann; Thomas Kick; Christoph Memmel; Andreas Pfingsten (Deutsche Bundesbank, 2010)
Section 340f of the German Commercial Code allows banks to provision against the special risks inherent to the banking business by building hidden reserves. Beyond risk provisioning, these reserves are implicitly accepted as an earnings management device. By analyzing financial statements of German banks for the period 1995 through 2009, we see these hidden reserves being used to (1) avoid a negative net income, (2) avoid a drop in net income compared to the previous year, (3) avoid a shortfall in net income compared to a peer group, and (4) reduce the variability of banks' net income over time. We (5) find a diminished relevance of avoiding a drop in net income as well as a shortfall relative to the peer group during the financial crisis. Finally, we are (6) unable to confirm any differences in the relevance of hidden reserves for earnings management between listed and non-listed banks.
Keywords: C23; G21; M41; 330; Earnings management; Income smoothing; Hidden reserves; Prospect theory; Financial institution; Bank; Bilanzpolitik; Stille Reserve; Prospect Theory; Schätzung; Deutschland